2021
DOI: 10.1111/ina.12840
|View full text |Cite
|
Sign up to set email alerts
|

Particle release and transport from human skin and clothing: A CFD modeling methodology

Abstract: Particle release from human skin and clothing has been identified as an important contributor to particulate matter burden indoors. However, knowledge about modeling the coarse particle release from skin and clothing is limited. This study developed a new empirically validated CFD modeling methodology for particle release and transport from seated occupants in an office setting. We tested three modeling approaches for particle emissions: Uniform; Uniform + Localized; and Uniform + Localized with Body Motion; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…An additional limitation of our study was the model’s relatively simplified representation of particle mass-transfer mechanisms. A more accurate representation could be accomplished with a physics-based computational fluid dynamics model, especially for scenarios involving close proximity between occupants (<1.4–1.6 m). , However, the substantial data and computational requirements of such models generally limit their applicability to deterministic scenarios involving a single, well-characterized environment with minimal human influence. In comparison, the approach used in this study was consistent with the limited data available for parameterization and facilitated a probabilistic characterization of variability requiring tens of thousands of executions of the algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional limitation of our study was the model’s relatively simplified representation of particle mass-transfer mechanisms. A more accurate representation could be accomplished with a physics-based computational fluid dynamics model, especially for scenarios involving close proximity between occupants (<1.4–1.6 m). , However, the substantial data and computational requirements of such models generally limit their applicability to deterministic scenarios involving a single, well-characterized environment with minimal human influence. In comparison, the approach used in this study was consistent with the limited data available for parameterization and facilitated a probabilistic characterization of variability requiring tens of thousands of executions of the algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…As such, an occupant’s thermal plume can be readily disrupted when they engage in nonsedentary activity. , Particles within the personal cloud of one occupant can also be transported into the breathing zones of other occupants (or “bystanders”) in the same microenvironment. This phenomenon has been referred to as “cross-contamination”. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clothing manufacturing mode based on a 3D model is also helpful for enterprises to realize exible production and reduce inventory pressure and capital chain tension. For consumers, a more intuitive clothing display can help them accurately judge whether the clothing is suitable for their own conditions, which greatly promotes clothing consumption [7][8][9][10]. For schools, 3D clothing simulation can serve teaching well.…”
Section: Introductionmentioning
confidence: 99%
“…This excess of air pollution beyond room background levels could be linked to proximity to air pollutant sources and personal activities (e.g., cooking, cleaning). 36 Beyond field campaigns, recent empirical studies in simulated offices revealed that human dermal emissions of particles 30,37 and respiratory emissions of CO 2 31 are also notable constituents of human personal clouds.…”
mentioning
confidence: 99%